Generation Z Entrepreneurship in Tourism Opportunity: An Interpretative Phenomenological analysis - Hutagalung, Husen; Rachman, Arief Faizal; Rahayu, Nurti; Hermawan, Yudan; Aryapranata, Aryawan; Pusparani, Pusparani; Rianto, Rianto; Riyadi, Agus; Budiman, Surya Fajar; Pradhipta, RMW Agie (Universitas Ahmad Dahlan, 2025)
This study aims to explore the psychological experiences of Generation Z entrepreneurs in Jakarta who seize opportunities in tourism-related businesses such as open trips, beauty services, laundry, culinary ventures, and souvenir shops. Using a qualitative phenomenological design, this research adopts an Interpretative Phenomenological Analysis (IPA) approach to understand how young entrepreneurs interpret their entrepreneurial journeys in a rapidly changing digital era. Five Gen-Z entrepreneurs participated in semi-structured interviews, and the data were analyzed through a hermeneutic and idiographic process to capture the depth of lived experiences. The analysis revealed three superordinate themes: (1) self-confidence, characterized by technological mastery and optimism in facing business challenges; (2) independence, reflected in their preference for freedom of expression and anti-hierarchical work culture; and (3) pragmatism, denoting a lifestyle-oriented pursuit of financial freedom and comfort. These findings contribute to a deeper understanding of Gen-Z entrepreneurial identity and offer practical implications for developing entrepreneurship education and character-building programs in both formal and informal educational settings.